Hot Cracking Phenomena in Welds III 2011
DOI: 10.1007/978-3-642-16864-2_6
|View full text |Cite
|
Sign up to set email alerts
|

Hot Tearing Sensitivity of Al-Mg-Si Alloys Evaluated by X-Ray Microtomography After Constrained Solidification at High Cooling Rate

Abstract: International audienceThe mechanical behavior of alloys resulting from a mixture of a AA6061 base alloy with different alloys from the Al-Si and Al-Mg series used as filler alloys during welding has been investigated under conditions close to welding. The specimens have been subjected to constrained solidification carried out at a high cooling rate of 80 K/s. In the test developed in this study, the central part of the specimen is initially melted. During solidification, this zone suffers strains only generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…By the study of student t results, we can observe that the method with the highest values is obtained for Method 5. The results obtained show a result that is consistent with previous results in the literature, since it has been determined that magnesium is the main element that influences the RPT values and is the element with the highest student t coefficient [20]. This method is the only one that indicates that silicon also has a statistical effect on the RPT values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…By the study of student t results, we can observe that the method with the highest values is obtained for Method 5. The results obtained show a result that is consistent with previous results in the literature, since it has been determined that magnesium is the main element that influences the RPT values and is the element with the highest student t coefficient [20]. This method is the only one that indicates that silicon also has a statistical effect on the RPT values.…”
Section: Discussionsupporting
confidence: 90%
“…The increase of percentage of alloying elements in an Al alloy decrease the solidification process related temperature until the minimum solidification temperature, which is reached in the eutectic composition. Giraud and his team [20] observed that the coalescence solid fraction is independent of Si content and depends on Mg content for AlSi 10 Mg alloys, because a solid skeleton is developed earlier in the Mg-rich alloys, like π-Al 8 Mg 3 FeSi 6 . The Fe and Ni as alloying elements can form β-Al 5 SiFe, Al 3 Ni, and Al 7 Cu 2 Fe needle like structures, that they can reduce the solid particles moving to pass each other, as shown in Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…It promotes faster rigidity, because it reduces the solidification time and because it hinders the movement of the remaining eutectic liquid. It has also been observed that Mg has an effect on increasing the coalescence of solid fraction, because a solid skeleton can develop earlier in Mg-rich alloys, such as the π-Al 8 Mg 3 FeSi 6 phase [51], preventing free movement of the remaining liquid. Mg 2 Si has a typical bone structure that restricts the movement of the remaining liquid.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 shows the A-values of the considered alloys as a function of their amount of silicon. It shows the typical -shaped curve [10] describing the susceptibility to hot cracking with a peak where the concentration of silicon is close to 1% as known from experiments with ring casting specimens [24,25] as well as from experiments on laser beam welding [26].…”
Section: Alloy-specific A-valuementioning
confidence: 99%